Expierimental models of portal hyperténsion - Pressa, Carlos; Porteiro, Alvaro; Uturbey, Judith; Ramírez, Wilson; Arèvalo, Ethel (Cirugía del Uruguay, 1979)
Analy.sis of IPethods fór experimental · production· of Portal Hypertension in dogs by means of Dimethylnitrqsamine, ligation· ·or- suprahepatic:' veins or botfi_. together.